THE EPIDEMIOLOGY OF PEDIATRIC CANCER IN THE PALLIATIVE CARE UNIT AT DR. SOETOMO GENERAL HOSPITAL, SURABAYA - Izzatul Fithriyah; Agustina Konginan; Margarita Maramis; Marlina Mahajudin; Nalini Muhdi; Hendy Margono; Endang Warsiki; Lestari Basoeki; Suksmi Yitnamurti (Universitas Airlangga, 2020)
Background: Children with cancer require special interventions and palliative care to improve their quality of life. The epidemiology of pediatric cancer is needed as a basis for determining health policy. Purpose: This study describes pediatric cancer patients in the palliative outpatient clinic in Dr. Soetomo General Hospital, Surabaya. Methods: This study is an observational descriptive study that uses the medical records of pediatric patients with cancer at the palliative care unit in Dr. Soetomo General Hospital between June 2014 and July 2015. The data included the demographic characteristics of the pediatric cancer patients and was analyzed using descriptive statistics. Results: The number of children in the 1–5 years, 6–10 years, and 11–15 years age groups was similar, while noticeably fewer children fell into the 16–18 years group. The majority of children suffering from cancer were male (68,70%). The most common type of cancer in was blood cancer (leukemia) with a percentage of 51.91%, while the rarest types were retinoblastoma and lymph node cancer (malignant lymphoma) with percentage of 3.05%. Conclusion: The incidence of pediatric cancer patients in the palliative outpatient clinic was quite high. These patients tended to be male, aged 6–10 years, and suffered from leukemia.